Analisis Kekuatan Kolom Beton Bertulang Dengan Penampang Persegi Dan Silinder Akibat Beban Ledakan (Blasting Loads) - Brian Priadana Mulrony; Reni Suryanita; Ismeddyanto Ismeddyanto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Bomb attack by terrorist in recent years had caused significant damage to structures, especially building structures. A bomb explosion within or nearby a building could cause huge damage toward structure even life loss. Due to the threat of bomb attack and it’s impact, it had become necessity to analyze the effect of blasting load on structures. One of solution that could be applied in order to decrease the impact was by strengthening the column element of a building. This research compared the column strength between cylinder column and square column. Each column had equal quality of concrete material and steel reinforcemenl. The purpose of this research was to conclude which type of column had better strength when subjected to blasting load. There were four portals variation used in this analysis, which each portal subjected to different parameter of blasting load. Parameter of blasting load used were 100 kg and 500 kg weight of TNT with 10 m and 15 m stand-off distance. The type of blasting load in this analysis was surface burst and its parameter calculated with ATBlast software. Beside variation of weight and stand-off distance, location of bomb planted also variated too, which were in front of and beside of building. Analysis result showed that among all of portal variation, the cylinder column had better strength than square column. It was proven by capacity design check and percentage of failed column. Based on analysis result, cylinder column type had smallest percentage of failed column with 6.06%, whereas the square column type had largest percentage of failed column with 59.60%.Keywords: Blasting loads, Reflection wave, Surface Burst, Interaction Diagram